Multifocal intraosseous pseudomyogenic (epithelioid sarcoma-like) hemangioendothelioma: A rare presentation of an uncommon tumor - Vishwapriya M. Godkhindi; Vidya Monappa; Sharada Mailankody; Umesh Velu; Shuiab M. V. Mohammed; Aisharya Banerjee (Indian Journal of Pathology and Microbiology, 2024)
Pseudomyogenic hemangioendothelioma (PHE) is an uncommon mesenchymal neoplasm of intermediate malignant potential showing endothelial differentiation. Around 20 cases of primary osseous PHE have been reported to date. A 16-year-old boy presented with complaints of pain in his right leg. Imaging revealed multifocal intramedullary and cortical-based lytic lesions involving long and small bones. Microscopic examination revealed plump, spindled cells arranged in fascicles and admixed “epithelioid” and “rhabdoid” cells sans vasoformative areas. By immunohistochemistry, the lesional cells were reactive for AE1/AE3, CD31, Erg, Fli1, and SMA, while immunonegative for CD34, myogenin, and S100. Nuclear expression of the INI1/SMARCB1 protein was retained. PHE is a rare entity, more so as a primary osseous lesion; therefore, awareness of the presence of this entity in the bone is the key to making a diagnosis. We discuss its clinicopathological features, differential diagnosis, and an attempt a short review of the literature.